Zooarchaeology in the Paraná River flood plain: GIS implementation at a regional scale - Sartori, Julieta Isabel (2014)
The aim of this study is to evaluate the use of wildlife resources that human populations which inhabited the Paraná River floodplain during the late Holocene carried out. To that end, zooarchaeological information from 26 archaeological sites analyzed by different research teams was collected. In order to perform the analysis of the composition of the sets, a Geographic Information System (GIS) is used, since this tool facilitates the comparison between the representations of the different taxa spatially and temporally. This allows us to establish similarities and differences in the use of wildlife resources carried out by the groups of hunters, gatherers and fishers in the region. Most of the zooarchaeological analyses are performed at a micro-regional level; however, due to the fact that this study is developed at a regional scale, it enables a comprehensive understanding of the structure of the different archaeofaunal assemblages in the diverse landscape units which make up the Parana River floodplain. The application of the GIS to this analysis provides simple graphics to visualize and interpret data and its variations in terms of space.